Scientific Argumentation Skills Through The Rasch Model on Analysis of Survey Data on The Importance of Aviation Vocational Education in Indonesia - Fitri Masito; I Gusti Agung Ayu Mas Oka; Catra Indra Cahyadi; Yeti Komalasari; Alfian Meidy Anes; Eko Risdianto (Journal of Innovation in Educational and Cultural Research, 2022)
This research aims to analyze the importance of scientific work skills in aviation vocational education in Indonesia using the Rasch Model. This research applies a mixed research methodology. The data collection tool in this study used reasoned test questions to uncover the argument skills of aviation vocational education cadets in Indonesia. The population taken in this study is aviation vocational education cadets in Indonesia. Sampling using purposive sampling techniques. The results of the analysis of reasoned question-answer analysis data entered with questionnaires are processed using the Winstep and Rasch Model applications. Analysis of cadet argumentation data is obtained at level 2 of 4 maximum levels. Argument skills at level 2 mean claiming with data. The results of deepening the scientific arguments of cadets obtained an alpha Cronbach value of 0.96 which belongs to a special category. The conclusion of Rasch model research applied to vocational education obtained cadet's argument skills on the plurality of claims with data.